Distortion and Compensation of Doppler Shift Characteristics of Vortex Beam Superposition Due to Rotating Rough Surfaces and Occlusion - Hongyang Wang; Zijing Zhang; Chengshuai Cui; Yuan Zhao (IEEE Photonics Journal)
We employed the signal-to-maximum sideband ratio (SMSR) to investigate the sideband interference and compensation of the rough surface target-derived scattering distortions and occlusion on the frequency shift characteristics of the vortex beams superposition in the rotational Doppler effect (RDE). The critical roughness, particularly the critical occlusion ratio hindering rotational Doppler shift (RDS) peak discrimination subject to phase distortion, are discussed in detail. Finally, the phase retrieval algorithm is employed to compensate the distortion induced by atmospheric turbulence, aiming to enhance the optical field purity, RDS peak amplitude and SMSR indicators. The simulations demonstrate that the ±2 order beam has a stronger capability to resist the dispersion effect of occlusion on the RDS peak discrimination, which is 57% higher than the lowest one. The average enhancement factor of SMSR for higher-order beam is 13.53-folds higher than that of lower orders. $C_n^2$ = 2 × 10−16 m−2/3 is the critical turbulence intensity that achieves a relative enhancement of the RDS peak amplitude. This research provides valuable insights for optimizing the precise measurement of rotational velocity in free-space RDE applications.